Spherical calcium oxide and preparation method thereof
By mixing nanoclay powder with high calcium content ore powder and preparing spherical calcium oxide, the existing problems of low strength and dust in calcium oxide are solved, and a high-strength and low-dusted calcium oxide desiccant is realized, suitable for food drying.
Patent Information
- Application Number
- CN202411338751.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
AI Technical Summary
The surface of existing spherical calcium oxide desiccants is prone to dust, has low strength and is easily damaged, making it difficult to meet the efficient drying needs of food drying.
Nanoclay ore powder is mixed with high calcium content ore powder, and spherical calcium oxide is prepared by sphere making, drying and calcining. Nanoclay ore powder is used as a binder to enhance particle strength and reduce dust content.
The prepared spherical calcium oxide strength is increased to 2.6-50N, the dust content is reduced to <20ppm, the surface is smooth, and the risk of damage is reduced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of desiccants, and in particular to spherical calcium oxide and a preparation method thereof. Background Art
[0002] Calcium oxide is a commonly used food desiccant in people's daily life. It is mainly made by pelletizing, calcining and screening natural mineral powders such as calcium carbonate and limestone to obtain spherical calcium oxide, which is then packaged into small bags with breathable paper and placed in food bags to absorb moisture in the air and ensure the dryness of the food in the packaging bag. The desiccant produced by this process is prone to dust on the surface and has low strength, so it is easy to break during use. Summary of the invention
[0003] The object of the present invention is to provide a spherical calcium oxide and a preparation method thereof. The spherical calcium oxide prepared by the present invention has low dust content, high strength and is not easy to break.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing spherical calcium oxide, comprising the following steps:
[0006] Mixing high calcium content mineral powder and nano clay mineral powder to obtain a mixture; the content of CaO in the high calcium content mineral powder is greater than 40%;
[0007] The mixed material is mixed with an auxiliary agent to form balls to obtain spherical particles;
[0008] The spherical particles are dried and calcined to obtain the spherical calcium oxide.
[0009] Preferably, the 200-mesh sieve residue of the nano-clay mineral powder is less than 10% by mass.
[0010] Preferably, the nano clay mineral powder includes one or more of bentonite powder, attapulgite powder, palygorskite powder, sepiolite powder, kaolin powder, laterite powder, bauxite powder, argillaceous earth powder and diatomaceous earth powder.
[0011] Preferably, the high calcium content mineral powder comprises one or more of marble powder, calcite powder, limestone powder, dolomite powder, quicklime powder and slaked lime powder; and the 200 mesh sieve residue of the high calcium content mineral powder is less than 10%.
[0012] Preferably, the mass content of high calcium content mineral powder in the mixture is 50-90%.
[0013] Preferably, the auxiliary agent includes one or more of water, water glass, aluminum sol aqueous solution and carboxymethyl cellulose aqueous solution.
[0014] Preferably, the mass of the auxiliary agent is less than 2% of the mass of the mixture.
[0015] Preferably, the drying includes shade drying, sun drying or oven drying.
[0016] Preferably, the calcination temperature is 450-900° C., and the holding time is 0.5-10 h.
[0017] The present invention provides spherical calcium oxide obtained by the preparation method described in the above scheme, with a strength of 2.6-50N and a turbidity of less than 20ppm.
[0018] The present invention provides a method for preparing spherical calcium oxide, comprising the following steps: mixing high calcium content mineral powder and nano clay mineral powder to obtain a mixture; the CaO content in the high calcium content mineral powder is greater than 40%; mixing the mixture with a binder to form balls to obtain spherical particles; drying and roasting the spherical particles to obtain the spherical calcium oxide desiccant. The present invention uses nano clay mineral powder as a binder, and the nano clay mineral powder has a high surface area, which increases the contact area with the high calcium content mineral powder, thereby increasing the strength of the spherical particles, while reducing breakage and reducing the dust content on the surface of the spherical calcium oxide. The results of the embodiment show that the spherical calcium oxide prepared by the present invention has high strength, reaching 2.6 to 50N, low dust content, and turbidity <20ppm. DETAILED DESCRIPTION
[0019] The present invention provides a method for preparing spherical calcium oxide, comprising the following steps:
[0020] Mixing high calcium content mineral powder and nano clay mineral powder to obtain a mixture; the content of CaO in the high calcium content mineral powder is greater than 40%;
[0021] The mixed material is mixed with an auxiliary agent to form balls to obtain spherical particles;
[0022] The spherical particles are dried and calcined to obtain the spherical calcium oxide.
[0023] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0024] The invention mixes high calcium content mineral powder and nano clay mineral powder to obtain a mixture.
[0025] In the present invention, the high calcium content mineral powder preferably includes one or more of marble powder, calcite powder, limestone powder, dolomite powder, quicklime powder and slaked lime powder; the mass of the 200 mesh sieve residue of the high calcium content mineral powder is less than 10%.
[0026] In the present invention, the nano clay powder preferably includes one or more of bentonite powder, attapulgite powder, palygorskite powder, sepiolite powder, kaolin powder, laterite powder, bauxite powder, argillaceous earth powder and diatomite powder; the 200 mesh sieve residue mass of the nano clay powder is less than 10%, and more preferably the 325 mesh sieve residue mass is less than 10%. In the present invention, the nano clay powder is either a natural nano clay, such as bentonite, attapulgite, palygorskite, sepiolite, or the mineral needs to be processed by nano treatment to form a nano clay powder, such as kaolin powder, laterite powder, bauxite powder, argillaceous earth powder and diatomite powder (these minerals are not natural nano clay). The present invention does not make special requirements for the nano processing, and the nano processing methods well known in the art can be used, such as high pressure homogenization, flaking, etc. In the present invention, since nanoparticles will agglomerate when dry, and there is no sieve with nano-scale aperture that can perform nano-scale screening in a dry state, 200 mesh screening is used to express it in production practice. In the present invention, the role of the nano-clay mineral powder is to act as a binder to bind high-calcium-containing mineral powder, and it also has the effects of strengthening, smooth surface and dust reduction, and easy ball formation. The present invention uses nano-scale clay mineral powder as a binder, which can increase the contact area with high-calcium-containing mineral powder, thereby improving the strength of spherical calcium oxide, while reducing breakage in the preparation process and reducing the dust content on the surface of spherical calcium oxide. In an embodiment of the present invention, the nano-clay mineral powder is a commercially available product.
[0027] The present invention has no special requirements for the mixing, and any method known in the art that can uniformly mix the two can be used. In the present invention, the mass content of the high calcium content mineral powder in the mixture is preferably 50-90%, specifically 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, which will not be exhaustively listed here.
[0028] After obtaining the mixed material, the present invention mixes the mixed material with an auxiliary agent to form balls, thereby obtaining spherical particles.
[0029] In the present invention, the auxiliary agent preferably includes one or more of water, water glass, aluminum sol aqueous solution and carboxymethyl cellulose (CMC) aqueous solution, and water glass is more preferred. In the present invention, the mass concentration of the water glass is preferably less than 10%; the concentration of the aluminum sol aqueous solution is preferably less than 1%; the mass concentration of the carboxymethyl cellulose aqueous solution is preferably less than 1%. In the present invention, the amount of the auxiliary agent is preferably less than 2% of the mass of the mixture, and more preferably 0.1-2%. In the present invention, the role of the auxiliary agent is to promote ball formation. When the auxiliary agent is water glass, it also has the function of improving the surface finish of spherical calcium oxide.
[0030] The present invention has no special requirements for the pelletization, and the pelletization process known in the art can be used. In the embodiment of the present invention, the mixed material is added intermittently in the spherical granulator, the additive is sprayed, the particles roll, eat powder, and gradually grow, and the particle rolling time is determined according to the required particle size range.
[0031] After the pelletizing is completed, the present invention preferably performs screening to obtain spherical particles of a desired size by controlling the diameter of the sieve.
[0032] After obtaining the spherical particles, the present invention dries and roasts the spherical particles to obtain the spherical calcium oxide.
[0033] In the present invention, the spherical particles are preferably first surface polished and then dried. In the present invention, the drying preferably includes shade drying, sun drying or oven drying; when the drying method is oven drying, the drying temperature is preferably 50 to 450°C. The present invention has no special requirements for the drying time, and it is sufficient to dry until the moisture content is less than 25%.
[0034] In the present invention, the calcination temperature is preferably 450-900°C, more preferably 500-850°C, and further preferably 600-800°C; the calcination holding time is preferably 0.5-10h, more preferably 2-5h; the calcination is preferably carried out in an air atmosphere. In the present invention, the calcination is preferably carried out in a rotary kiln or a static drying kiln. The present invention removes excess moisture through calcination, performs ceramicization, and improves the structural strength of the particles.
[0035] The present invention provides spherical calcium oxide prepared by the preparation method described in the above scheme, with a strength of 2.6-50N and a turbidity of less than 20ppm.
[0036] In the present invention, the physicochemical parameters of the spherical calcium oxide are as follows:
[0037] Shape: spherical;
[0038] Color: light yellow or grayish white;
[0039] Water absorption (25℃ / 75%RH / 48H): 10-30%; specifically 19%, 21% or 22% in the embodiment; the test method refers to "JC / T 2072-2011 Desiccant for Insulating Glass";
[0040] Bulk density: 0.5-1.0 g / mL; specifically 0.90 g / mL, 0.92 g / mL or 0.95 g / mL in the embodiment; the test method refers to "JC / T 2072-2011 Desiccant for Insulating Glass";
[0041] Strength: 2.6-50N; specifically 20N, 15N, 25N in the embodiment; the test method refers to "JC / T 2072-2011 Desiccant for Insulating Glass";
[0042] Gas desorption volume: less than 0.3mL / g; specifically 0.12mL / g, 0.15mL / g or 0.18mL / g in the embodiments; the test method refers to "JC / T 2072-2011 Desiccant for Insulating Glass";
[0043] Temperature rise: greater than 35°C; the test method refers to "GB / T10504-20173A-Molecular Sieve";
[0044] Moisture content of finished product (350℃): less than 1.5%; the test method refers to "JC / T 2072-2011 Desiccant for Insulating Glass".
[0045] The spherical calcium oxide and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0046] Example 1
[0047] 65% of dolomite powder (with a particle size of 200 meshes and 95% passing) and 35% of nano-kaolin powder (with a particle size of 325 meshes and 95% passing) are mixed to obtain a mixture, and a 0.5% concentration of water glass solution (the added mass is 0.1% of the mass of the mixture) is sprayed into a spherical granulator, and the mixture is added intermittently, and the particles roll, eat powder, and gradually grow. The particle rolling time is determined according to the required particle size range; when the required particle size is reached, the particle material is taken out of the granulator, sieved, and the diameter of the sieve is controlled to obtain spherical particles with a certain particle size range; and then the surface is polished and dried, and the particles are roasted in a rotary kiln, and the temperature of the rotary kiln is controlled at 900-950° C. The obtained particle product is tested for physical and chemical properties. Particle size: 1.5-2.0mm; shape: spherical; color: grayish white; water absorption (25℃ / 75%RH / 48H): 21%; bulk density: 0.90g / mL; strength: 20N; gas desorption: 0.15mL / g; temperature rise: 65℃; finished product moisture content (350℃): 0.5%. Turbidity: 12ppm.
[0048] Example 2
[0049] 70% of limestone powder (with a particle size of 200 meshes and 98% passing) and 30% of nano bentonite powder (with a particle size of 325 meshes and 98% passing) are mixed to obtain a mixture, and a 1% aluminum sol solution (the added mass is 0.2% of the mass of the mixture) is sprayed into a spherical granulator, and the mixture is added intermittently, and the particles roll, eat powder, and gradually grow. The particle rolling time is determined according to the required particle size range; when the required particle size is reached, the particle material is taken out of the granulator, sieved, and the diameter of the sieve is controlled to obtain spherical particles with a certain particle size range; and then the surface is polished and dried, and the particles are roasted in a rotary kiln, and the temperature of the rotary kiln is controlled at 850-920° C. The obtained particle product is tested for physical and chemical properties. Particle size: 1.5-2.0mm; shape: spherical; color: grayish white; water absorption (25℃ / 75%RH / 48H): 22%; bulk density: 0.95g / mL; strength: 15N; gas desorption: 0.18mL / g; temperature rise: 70℃; finished product moisture content (350℃): 0.9%. Turbidity: 9ppm.
[0050] Example 3
[0051] 65% of quicklime powder (with a particle size of 200 mesh and 99% passing) and 35% of nano-attapulgite powder (with a particle size of 325 mesh and 96% passing) are mixed to obtain a mixture. A 0.5% CMC solution (the added mass is 0.1% of the mass of the mixture) is sprayed into a spherical granulator. The mixture is added intermittently, and the particles roll, eat powder, and gradually grow. The particle rolling time is determined according to the required particle size range. When the required particle size is reached, the particle material is taken out of the granulator, sieved, and the diameter of the sieve is controlled to obtain spherical particles with a certain particle size range. After surface polishing and drying, the particles are roasted in a rotary kiln. The temperature of the rotary kiln is controlled at 820-920° C. The obtained particle product is tested for physical and chemical properties. Particle size: 1.5-2.0mm; shape: spherical; color: grayish white; water absorption (25℃ / 75%RH / 48H): 19%; bulk density: 0.92g / mL; strength: 25N; gas desorption: 0.12mL / g; temperature rise: 68℃; finished product moisture content (350℃): 0.3%. Turbidity: 18ppm.
[0052] Comparative Example 1
[0053] 65% dolomite powder (with a particle size of 200 meshes and 95% passing) and 35% kaolin powder (with a particle size of 325 meshes and 95% passing) are mixed to obtain a mixture, and a 0.5% water glass solution (the added mass is 0.1% of the mass of the mixture) is sprayed into a spherical granulator, and the mixture is added intermittently, and the particles roll, eat powder, and gradually grow. The particle rolling time is determined according to the required particle size range; when the required particle size is reached, the particle material is taken out of the granulator, sieved, and the diameter of the sieve is controlled to obtain spherical particles with a certain particle size range; and then the surface is polished and dried, and the particles are roasted in a rotary kiln, and the temperature of the rotary kiln is controlled at 900-950° C. The obtained particle product is tested for physical and chemical properties. Particle size: 1.5-2.0mm; shape: spherical; color: grayish white; water absorption (25℃ / 75%RH / 48H): 20%; bulk density: 0.95g / mL; strength: 10N; gas desorption: 0.18mL / g; temperature rise: 62℃; finished product moisture content (350℃): 0.5%. Turbidity: 25ppm.
[0054] It can be seen from the above examples and comparative examples that the present invention uses nano-clay mineral powder to prepare spherical calcium oxide with low dust content and high strength.
[0055] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing spherical calcium oxide, characterized in that: The following steps are involved: Mixing high calcium content mineral powder and nano clay mineral powder to obtain a mixture; the content of CaO in the high calcium content mineral powder is greater than 40%; The mixed material is mixed with an auxiliary agent to form balls to obtain spherical particles; The spherical particles are dried and calcined to obtain the spherical calcium oxide.
2. The preparation method according to claim 1, characterized in that: The 200-mesh sieve residue of the nano-clay mineral powder is less than 10% by mass.
3. The preparation method according to claim 1 or 2, characterized in that: The nano clay mineral powder includes one or more of bentonite powder, attapulgite powder, palygorskite powder, sepiolite powder, kaolin powder, laterite powder, bauxite powder, argillaceous earth powder and diatomaceous earth powder.
4. The preparation method according to claim 1, characterized in that: The high calcium content mineral powder comprises one or more of marble powder, calcite powder, limestone powder, dolomite powder, quicklime powder and slaked lime powder; the mass of the 200 mesh sieve residue of the high calcium content mineral powder is less than 10%.
5. The preparation method according to claim 1 or 4, characterized in that: The mass content of high calcium content mineral powder in the mixture is 50-90%.
6. The preparation method according to claim 1, characterized in that: The auxiliary agent includes one or more of water, water glass, aluminum sol aqueous solution and carboxymethyl cellulose aqueous solution.
7. The preparation method according to claim 1 or 6, characterized in that: The mass of the auxiliary agent is less than 2% of the mass of the mixture.
8. The preparation method according to claim 1, characterized in that: The drying includes shade drying, sun drying or oven drying.
9. The preparation method according to claim 1, characterized in that: The calcination temperature is 450-900° C., and the heat preservation time is 0.5-10 hours.
10. The spherical calcium oxide obtained by the preparation method according to any one of claims 1 to 9 has a strength of 2.6 to 50N and a turbidity of less than 20ppm.
